DINAMIKA JARINGAN INTELEKTUAL PESANTREN DI SULAWESI SELATAN - Arief, Syamsuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
The dynamic of Muslim scholars’ network between South Sulawesi (boarding school) and Haramains is believed to be a factor influencing the discourse of intellectual and Islamic tradition in South Sulawesi in the 20th century. The “traditional Yellow Book” and intensive networking formed a new community consisting of the pilgri-mages, Muslim scholars, boarding school students and the big and growing number of traders. The implication of the networking can be seen from the "halaqah" model originally started in Masjid al-Haram in Mecca and Masjid al-Nabawi in Madinah, then in houses called “Dar al-Arqam”. In the context of South Sulawesi, As‘adiyah Board-ing school in Sengkang was considered to be the starting point of the development of boarding school in the 20th century. This development was due to genealogic, ideological, and Yellow Book network, as well as social and political network.